Minimally Invasive Methods for Treatment of Periodontal Defects: A Case Report - Krastev, Bogdan Petrov (The Journal of Dentists, 2014)
Treatment of periodontal diseases is a complex issue because of the difficult access to the root surface. Both the surgical and the nonsurgical method have their importance and place in the treatment of periodontal diseases. Nonsurgical treatment can be used independently, as a definitive or as a preparation for the surgical treatment. Access-Open flap surgery is the gold standard for treating periodontal diseases. Objectives: To demonstrate the possibilities of two minimally invasive methods-Minimally Invasive Surgery Technique performed with Er:YAG lazer and Regenerative Ultrasonic Periodontal Endoscopy for treating chronic periodontitis. Methods: Female patient age 45 was diagnosed with chronic periodontitis after X-ray examination. On her second lower molars the following pathology was found Probing Pocket Depth=6mm and infraossal defects with INFRA=3mm. Tooth 47 was treated with open flap curettage with an Er:YAG laser by the Minimally Invasive Surgery Technique. Regenerative Ultrasonic Periodontal Endoscopy was performed on tooth 37. The root surfaces of 36 and 37 were manipulated under indirect visual control and continuous irrigation with the help of periodontal endoscope DV2 Perioscopy System™ and ultrasonic tips EMS®, scaler Piezon Master 400®. Results: After a period of one year the following results were achieved: 1) No bleeding on probing. 2) Probing Pocket Depth 3mm 3) Complete bone regeneration-fill 4) Less gingival recession with RUPE. Conclusions: Based on the outcome of the minimally invasive procedures, they can be recommended as suitable and alternatives to the standard nonsurgical and surgical techniques.